STRATEGI KONSERVASI CANDI PENINGGALAN HINDU DI PULAU JAWA DENGAN MEMANFAATKAN WEB GIS CONSERVATION STRATEGY FOR LEGACY HINDU TEMPLE IN JAVA USING WEBGIS (Information Technology and Telematics, 2015)
Abstract— Java has a heritage of Hindu temples widespread since hundreds of years ago and has a high historical value as a place of worship religious buildings of archaeological heritage this ancient historical witness Hindu-Buddhist civilization building. Conservation Strategy that is the essential purpose in providing a coherent and integrated approach in the management aspects cultural heritage, so that people and the tourists still see it in the future, also give their views to the authorities to be able to take action to hold them. Hindu temple relics GIS application was created to assist the conservation or preservation strategies ancient relics in Java and make it easier to find a wide range of information about Relics widespread Hindu temple in Java. By providing a variety of features to be used by the user or the user to know the various info and point the location where the temple this comes as well as several temples search based on a predetermined radius from the center point. And that this application can continue to grow all the information in it, this application is added to the content of contacts that can provide input for these applications evolve.